ARCHITECTURAL PRACTICES OF PROJECT COMMUNICATION MANAGEMENT IN IRAQ - Al-Mayahi, Hala Taleb; Ismail, Syuhaida; Wahab, Mohammad Hussaini; Wan Mohd Rani, Wan Nurul Mardiah; Che Amat, Rohayah (PLANNING MALAYSIA, 2018)
Architects are significant initiators for the built environment projects, while architecture is all about communicating effectively with clients. Yet, some problems occur in regard to the mutual transfer of project information between those two parties. Thus, it is essential to enrol a proper system for managing project communication through communication management. Communication management is a notable part of the project management body of knowledge that coordinates and manages the process of exchanging information of the designing projects. However, studies confirmed that practices of communication management are often underestimated and overlooked. This article discusses communication management from architects’ perspectives with the objectives of determining the current practice in Iraq and examining the required communication competencies to improve it. An online questionnaire survey was administered via surveymonkey.com to 100 architects working in private firms in Basra City, south of Iraq. The collected data were analysed with Statistical Package of Social Sciences (SPSS) version 23. The analyses for the two objectives showed that Iraqi architects have little information and knowledge in project communication management, where standards and methodologies are not followed. The results also indicated the top-rated competencies to be obtained. Thus, this article concludes that there is a need to introduce communication management as an evolving knowledge area to the architects in Iraq, and develop its implementation through communication competencies that attempt to fulfil clients’ requirement and aspirations regarding the architectural design.